Far-infrared Tamm polaritons in a microcavity with incorporated graphene sheet - Silva, J. M. S. S. (2019)
Tamm polaritons (TPs) are formed at the interface between a semi-infinite periodic dielectric structure (Bragg mirror) and another reflector. They couple to elementary excitations in the materials that form the interface, such as metal plasmons or semiconductor excitons. Here we discuss the formation of TPs in the far-infrared spectral range, in the optical-phonon reststrahlen band of a polar semiconductor such as GaAs, attached to a Bragg reflector (BR). Their dispersion relation and the frequency window for the TP existence are calculated for a GaAs-BR interface. Microcavity structures containing a gap between the two reflectors are also considered, including those containing an inserted graphene layer and the possibility of tuning of the TP states by changing the graphene’s Fermi energy is demonstrated.